An Energy-Efficient Cyclic Diversionary Routing Strategy against Global Eavesdroppers in Wireless Sensor Networks - Ju Ren; Yaoxue Zhang; Kang Liu (International Journal of Distributed Sensor Networks)
While many protocols for sensor network security provide confidentiality for message content, contextual information usually remains exposed, which can be critical to the mission of the sensor network. In this paper, we propose an energy-efficient cyclic diversionary routing (CDR) scheme against global eavesdroppers for preserving location privacy and maximizing lifetime of wireless sensor networks (WSNs). To ensure no impact on lifetime of WSNs, we minimize the energy consumption of hotspots and generate abundant diversionary routing paths in areas far from sink. To enhance the location privacy preservation, we theoretically figure out the probability of the cyclic interference routings in different areas of the network and statistically achieve an energy consumption balance in the entire network. Analysis and simulation results show that CDR significantly improves the security in source-location privacy preservation without reducing the network lifetime.